Ameliorative Effect of Gastrodin on Aging and Inflammation of BV2 Cells by Regulating SIRT3 - Tong GUAN; Lisha GAO; Dezhi SUI; Jia MI; Binsheng WANG (Shipin gongye ke-ji, 2022)
Objective: In order to explore the protective effects and mechanism of gastrodin on BV2 cells treated with D-galactose. Methods: The BV2 cells were treated with D-galactose at different concentrations (10, 20, 30 and 40 μg/mL) for 24 h to establish a senescent cell model, and the optimum concentration of D-galactose was selected by CCK-8 method; The cells were divided into control group, model group, silent mating type information regulation 2 homolog 3 (SIRT3) inhibitor+gastrodin group and gastrodin group; and the optimum concentration of D-galactose was selected by CCK-8 method; The effects of different concentrations of gastrodin (10, 20, 30, 40 and 50 μg/mL) on the viability of BV2 cells treated with D-galactose were detected by CCK-8 method, and the best concentration of gastrodin was selected; The aging area of BV2 cells was detected by Senescence β-Galactosidase staining (SA-β-Gal); The level of reactive oxygen species (ROS) in BV2 cells was detected by biochemical method; The levels of neuroinflammatory factor interleukin 1β (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor α (TNF-α) were detected by enzyme linked immunosorbent assay (ELISA); The fluorescence intensity of SIRT3 was detected by immunofluorescence method; The protein expression levels of SIRT3, P16 and P21 were detected by Western blot. Results: Treatment with D-galactose at 30 μg/mL exerted a significant inhibitory effect on BV2 cell viability, resulting in SA-β-Gal staining area and the expression of aging proteins P16 and P21 increased (P<0.01), ROS level and inflammatory factor IL-1β, IL-6 and TNF-α significantly increased (P<0.01), and the expression of SIRT3 protein and fluorescence intensity decreased in BV2 cells (P<0.01). 30 μmol/L gastrodin significantly increased the of BV2 cells viability treated with D-galactose (P<0.01); Gastrodin reduced SA-β-Gal staining area and the expression levels of aging proteins P16 and P21 (P<0.01); Gastrodin significantly decreased the level of ROS and neuroinflammatory factor IL-1β, IL-6 and TNF-α; The expression level of SIRT3 protein in cells was significantly increased (P<0.01). Treatment with gastrodin increased the fluorescence intensity and protein levels of SIRT3. Conclusion: Gastrodin increased the viability of the BV2 cells treated with D-galactose, improved the SA-β-Gal staining area and aging protein P16 and P21 expression, reduced the ROS level and slowed down the inflammatory response, which may be related to its increasing effect on the expression of SIRT3 protein.